Reimplantation of multifocal intraocular lens (mIOL) (clinical case) - V. V. Teplovodskaya; N. A. Morina; A. D. Tagirova; E. P. Sudakova (Офтальмохирургия, 2018)
Purpose. Describe one of the possible causes of the photic phenomenas appearance and decrease in visual acuity after implantation of a mIOL. Also note the importance of accurate compliance with operation technique when using this type of lenses.Material and methods. Patient V., 46 years old, visited the S. Fyodorov Eye Microsurgery Clinic with complaints on decrease of visual acuity at distance and intermediate and the occurrence of photic phenomena. These complaints appeared 1 week after an implantation of the IOL OD (Lentis Mplus LS-313 MF30 20.5 D). In case of medical mydriasis noted that the diameter of capsularhexis was bigger than the recommended values and was decentralized, which led to the displacement of the lens haptics in the ciliary sulcus during the development of capsular fibrosis and the appearance of photic phenomena. On the ultrasound biomicroscopy (UBM) of OD IOL was in the capsule bag, for 6-7 hours the haptics partially contacts with the ciliary processes, for 12-13 hours in the ciliary sulcus and contacts with the iris pigment epithelium. Due to the patient’s dissatisfaction with the results of the previous operation, taking into account active lifestyle and unwillingness to use glasses, it was decided to replace the IOL with AcrySof® IQ PanOptix® Toric.Results. The surgery and the postoperative period proceeded without any complications. Visual acuity OD was 1.0. Due to the satisfaction of the patient after the surgery, it was performed cataract surgery in the left eye with the implantation of AcrySof® IQ PanOptix® 22 D.Conclusion. It is necessary to plan the operation carefully, including implantation of the multifocal IOL, as well as strictly follow the operation technique that was demonstrated in this clinical case.